Model kebijakan strategis pengelolaan lingkungan kawasan industri (Studi Kasus Kawasan Industri Jababeka dan EJIP di Kabupaten Bekasi) - Temmy Wikaningrum; Rijal Hakiki (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
The model of key factors contributing to support sustainability of the environmental management in the industrial estate were studied. These factors were the result of the prior research of prospective analysis that classified as the leverage factors and the driving factors. These factors were studied by the Analytical Hierarchy Process (AHP) as the criteria and alternatives input to elaborate the priority in the model of environmental management. AHP matrices were analyzed by purposive expert in the depth interview procedure. The analysis result showed that the industrial estate manager is the most important as the firts actor in the model (63.7%), the second actor is the industrial company as the tenant of the first actor (25.8%), and third actor is the local government (10.5 %). The priority of the dimension of the model in a row were economic (38.1%), social (19.4%), institutional management (19.3%), ecology (13.8%) and technology (9.4%). For developing the model there were five driving factors that develop the alternatives of the policy for achieving the goal. The priority of the alternatives in a row were improving the quality of industrial wastewater (29.5%), improving wastewater quality of integrated wastewater treatment plant outlet of the estate manager facility (21.5%), obtaining the industrial water demand (19.1%), conducting 3R (reduce, reuse and recycle) program of hazardous waste, and maintaining and supporting employed people in condusive work environment. By AHP result which resulting the priority of actors, dimensions, and alternatives, the model was developed effectively.